The Law of One Price and Arbitrage on China's Dual-listings - Liu, Li Xian; Bogomolov, T. (??, 2013)
Traditionally, arbitrage refers to simultaneously buying and selling the same financial assets by taking advantage of a price difference in two or more markets. However, the strict sense of arbitrage is hardly obtained after consideration the issues concerning transaction costs and time value of money. By using the identical assets such as Chinese ADRs and their underlying securities traded in different markets in Hong Kong in HK dollar and in New York in US dollar and by constructing a very simple arbitrage trading strategy, this study demonstrates that arbitrage profits are still available with monthly return ranging from 0.5 per cent to 3.8 per cent after considering transaction costs and non-overlap trading time issues. This is a new study to verify this behaviour of an emerging market’s ADRs traded in two financial market locations, so adding evidence of inefficiency in trading of China-listed stocks in foreign locations.